Educação e "interdisciplinaridade": uma análise da inserção do/a assistente social e do/a psicólogo/a no espaço escolar. - França, Sandra Carla Pereira de Lima (2019)
This thesis aims at understanding how the insertion of the social worker and the psychologist contribute to the answers regarding the psychosocial demands in the High School of Arts and Crafts. We built its proposal based on the experience in the Extension Project entitled Education and Citizenship, done by the Social Service course of the Catholic University of Pernambuco in 2016. In this project, based on weekly activities such as workshops, exhibition and discussion of videos, dialogues. and lectures, we aimed at providing students with reflections related to daily life, not only at school, but also related to the familiar and community contexts. The proposal was to promote the construction of values that would contribute to the citizens' formation of the participants, founded on the understanding of education beyond formal education. Thus, to problematize the thesis proposal, we start from the assumption that the school reality is affected by the psychosocial dynamics and presents demands that go beyond the teaching-learning process. Violence, the teacher-student relationship, family conflicts, bullying and drugs are some examples of those psychosocial phenomena that permeate the school environment, influencing their context. As we understand that those demands require an interdisciplinary professional performance that provides a broad reading of reality and contributes to the reflection and construction of a work proposal that encompasses the complexity of this school daily life, in this thesis we propose to take as the field- theme the interdisciplinarity within the school context, seeking to understand how the interaction Social Work and Psychology can respond to the psychosocial demands that emerge in this field. In this sense, the thesis took into account the cartographic method of analysis and, with a qualitative approach, adopted as research resources the narrative interview, the ludic group and the observation of the demands identifyed with the students, raised in the relationships and experiences that pervade the reality of that particular audience at school. As research subjects we interviewed: 4 (four) managers (principal, vice-principal, pedagogical coordinator and educational advisor), 4 (four) professionals, being 1 (one) psychologist of the school staff, 1 (one) psychologist and 2 (two) social workers who perform social projects at school, one (1) volunteer from the Education and Citizenship extension project and two (2) school teachers. The ludic group, in turn, was performed by 8 (eight) students who participated in the extension project. In its development, the research led us to an analysis of education as a field of professional action of interdisciplinary dimension that requires, at school, strategies and interventions which include the scope of their demands and the innovations of the current educational process, a reflection on the importance of extension and its contribution to the professional qualification, as well as the discussion of the approaches and specificities between the profession of Social Work and Psychology in a context marked by a frequent joint action.